Evaluation of potential drug-drug interactions in cancer patients at a tertiary care hospital in Pakistan. (April 2022) - Choudary, Nida Ashraf; Khan, Asad; Wahid, Abdul; Abubakar, Muhammad; Atif, Muhammad; Ahmad, Nafees
Background: Despite harboring a high burden of cancer patients who are at high risk of potential drug-drug interactions (pDDIs), there is scarcity of published information about pDDIs in cancer patients from Pakistan. Objective: To evaluate frequency, pattern, mechanism and factors associated with pDDIs in cancer patients treated at a tertiary care hospital in Pakistan. Methods: In this cross-sectional analytical study, a total of 253 eligible ambulatory cancer patients treated at Center for Nuclear Medicine and Radiotherapy Hospital Quetta were evaluated for pDDIs using IBM Micromedex® Drug Interactions. SPSS (version 26) was used for conducting multivariate analysis to find factors associated with the presence pDDIs. A p-value <0.05 was considered statistically significant. Results: A total of 141/253 (55.7%) patients were exposed to at-least one pDDI. A total of 251 pDDIs were noted with a median of one pDDI/per patient (interquartile range:1–2) Majority interactions were of major severity (72.9%), pharmacodynamic (49.8%) and had fair documentation level (64.1%). Anti-cancer drugs were involved in 73.0% pDDIs with doxorubicin as the most commonly involved (40.0%) anti-cancer followed by cyclophosphamide (27.6%) and cisplatin (13.5%). Potential cardiac adverse events made the bulk (33.8%) of predicted events. Receiving >2 anti-cancer (OR = 5.19, p-value = 0.001) and >6 ancillary drugs (OR = 4.16, p-value = 0.033) emerged as the risk factors of pDDIs. Conclusions: The prevalence of pDDIs was within the range reported in published literature. Solid medication review, availability of DDI detecting tools and clinical pharmacist, and paying special attention to the high-risk patients may reduce the frequency of pDDIs at the study site.